Monnet's Error? - Luigi Guiso; Paola Sapienza; Luigi Zingales (London School of Economics and Political Science (LSE), European Institute, 2014)
Do partial steps toward European integration generate support for further steps or do they create a political backlash? We try to answer this question by analyzing the cross sectional and time series variation in pro-European sentiments in the EU 15 countries. The two major steps forward (the 1992 Maastricht Treaty and the 2004 enlargement) seem to have reduced the pro-Europe sentiment as does the 2010 Eurozone crisis. Yet, in spite of the worst recession in recent history, the Europeans still support the common currency. Europe seems trapped in catch-22: there is no desire to go backward, no interest in going forward, but it is economically unsustainable to stay still.
Keywords: 330